2022
DOI: 10.3389/fped.2022.921880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Children With SARS-CoV-2 Infection in a Hospital in Latin America

Abstract: Objective:COVID-19 infections have shown a different behavior in children than in adults. The objective of this study was to describe the clinical characteristics and severity of SARS-CoV-2 infection in pediatric patients seen at a reference hospital in Colombia.MethodA descriptive, observational study in patients under the age of 18 years with a positive test for SARS-CoV-2 infection (RT-PCR or antigen) between April 2020 and March 2021. Multiple variables were studied, including demographic data, clinical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The population in this study demonstrated confirmed COVID-19 cases being slightly higher in males (51.4%), similar to other studies such as Martínez-García et al (59.3%), Olivar-López et al (53%), Nachega et al (52.4%), Aragón-Nogales et al (55.2%), Niño-Serna et al (54%) ( 23 27 ). Contrary to what was described in the literature, we found scholars as the most infected group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The population in this study demonstrated confirmed COVID-19 cases being slightly higher in males (51.4%), similar to other studies such as Martínez-García et al (59.3%), Olivar-López et al (53%), Nachega et al (52.4%), Aragón-Nogales et al (55.2%), Niño-Serna et al (54%) ( 23 27 ). Contrary to what was described in the literature, we found scholars as the most infected group.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to what was described in the literature, we found scholars as the most infected group. A few studies proved that children older than twelve years had a higher frequency of testing positive for COVID-19 ( 13 , 15 , 27 ). Martínez-García et al reported infants under five years with a more extensive distribution among all infected groups ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, acute severe and critical cases and severe complications related to COVID-19 infection, MIS-C were reported with high impact in the pediatric population in our study, similarly reported in other countries ( 35 ). Pediatric studies show that patients with comorbidities have more risk of severe disease; we found underlying diseases in 28%, as reported by Niño and cols ( 36 ). Other pediatric series from Latin America and other countries showed similar data ( 37 ).…”
Section: Discussionsupporting
confidence: 88%
“…We also identified a report of a severe pneumonia case in a 63year-old man on 22-Nov-2019 from Xiangyang, Hubei, who was medically evacuated to Wuhan. The data identified schools as the most common outbreak setting, which suggests other respiratory viruses in these cases, as children generally experience milder COVID-19 illness compared to adults, though moderate or severe COVID-19 disease and school outbreaks can still occur in children [33][34][35][36][37]. These cases could also reflect lack of testing for known pathogens.…”
Section: Discussionmentioning
confidence: 95%